New approach to increasing rice (Oryza sativa L.) lodging resistance and biomass yield through the use of growth retardants - Mukherjee, Dr Dhiman (Journal of Cereal Research, 2021)
Yield losses in rice are heavy, particularly when lodging occurs after heading. Lodging is due to the interaction between susceptibility to the lodging of the plant and external force.  A major contributing factor towards lodging is the tall phenotypic characteristic of the plant. In all cases, the plant stem base is unusually weak with a reduced diameter.  In rice, the application of growth retardant can reduce plant height by means of internodes retardation. This study, evaluate the use of two plant growth regulators as mepiquat chloride (N,N-dimethyl piperidinium chloride) and paclobutrazol [(2 RS, 3RS)-1-(4-chlorophenyl)-4-4-dimethyl-2(1,2,4-triazol-I-yl)-pentan-3-ol], which are synthetic plant growth regulators that showed reliable stem shortening to combat abiotic stress.  The present investigation was carried out under the aegis of Bidhan Chandra Krishi Viswavidyalaya during Kharif season of 2017 to 2019 in randomized block design with four replication comprised of ten treatments which include five levels of mepiquat chloride (37.5,50, 62.5, 75 and 100 g a.i. ha-1), four levels of paclobutrazol (25, 50, 75 and 100 g a.i. ha-1) and untreated control (water only). Foliar-applied growth retardant inhibited plant growth and retarded internode and culm length but increased culm diameter. Significantly more grain yield was observed with the mepiquat chloride @ 50 g a.i. ha-1 (47.34 q ha-1) and was at par with the paclobutrazol @ 25 g a.i. ha-1 (44.09 q ha-1) and paclobutrazol @ 50 g a.i. ha-1  (45.94 q ha-1).The result indicated that mepiquat chloride reduced plant height and the incidence of lodging and similarly improved yield over the control by 27 q ha-1. The highest straw yield was obtained either at paclobutrazol @ 50 g a.i. ha-1 and was at par only with the paclobutrazol @ 25 g a.i. ha-1 and statistically better to other treatments. Economics revealed that more net return (Rs. 35,421 ha-1  and B:C (1.87) observed with the mepiquat chloride @ 50 g a.i. ha-1 and was closely followed by paclobutrazol @ 25 g a.i. ha-1 and paclobutrazol @ 50 g a.i. ha-1.